ENHANCING THE SHELF LIFE OF BELL PEPPERS THROUGH DIFFERENT NATURAL EXTRACTS - ASLAM, I; ANEES, M; ANJUM, S; ABBAS, G; ABBAS, T; MAQSOOD, S; TALHA, M; SARWAR, M; GULRAIZ, CZ; ASHRAF, MI; UZAIR, M (Biological and Clinical Sciences Research Journal, 2024)
Bell pepper is a highly valued vegetable for its rich nutritional profile, containing essential vitamins. Similar to other perishable items, it starts to degrade after being harvested. For the improvement of the quality and shelf life of bell pepper vegetables, this experiment was conducted at the “Postharvest Lab. of Department of Horticulture, University of the Punjab, Lahore” study was comprised of various edible coatings of natural extracts, including aloe vera gel, neem leaf extract, garlic extract, ginger extract, and lemongrass leaf extract applied on capsicum vegetable at room temperature for 8 days, and data was recorded regularly. Various parameters such as weight loss, firmness, total soluble solids (TSS), total phenolics, ash content, pH, color, and appearance were measured. Bell pepper treated with edible aloe vera gel extract and ginger extract coatings showed significant improvements in firmness and minimum weight loss compared to untreated (control T0). The data were analyzed using a two-factor factorial ANOVA, and treatment means were compared using the LSD test at the 5% probability level.